(untitled) (Annals of Medical Research, 2021)
Aim: The glenoid rim fractures, bony bankart lesions and/or tuberculum majus fractures that occurred due to snowboarding-related first-time shoulder dislocations may have differences specific to these athletes. Thus, we aimed to examine the characteristics of bone lesions in cases with snowboarding-related first-time shoulder dislocation. Materials and Methods: The cases diagnosed with first-time shoulder dislocation and received a closed reduction in the emergency department between 2018 and 2020 were examined retrospectively. 18 patients with snowboarding-related dislocation, and 24 patients with first-time shoulder dislocation by a different injury mechanism other than winter sports injury mechanism were included in the study. Those with snowboarding-related injuries were classified as Group A and other cases were classified as Group B. Comparison was made between the two groups. Results: The average age was 27.11 ± 6.14 years in Group A, and 26.17 ± 5.44 years in Group B (p:0.656). There were 12 men (M) and 6 women (W) in Group A, and 16 M and 8 W in the Group B (p:0.999). The two groups were similar in terms of Hill-Sachs lesion, tuberculum majus fracture, bony bankart lesion, and additional injury (p>0.05). In the snowboarders, a relationship was found between the injured side and the lead foot (p: 0.013). There was a significant difference between the injury mechanism and the presence of Hill-Sachs lesion in the snowboarders (p:0.033). Conclusion: The characteristics of bone lesions in snowboarding-related first-time shoulder dislocations may be similar to that of shoulder dislocations occurred by different mechanisms. In snowboarding, the direction of sliding may put the shoulder at a higher risk of dislocation for a particular side. For these athletes, the injury mechanism may be a factor affecting the formation of Hill-Sachs lesion.